Geographic Differences in the Earnings of Economics Majors - John V. Winters; Weineng Xu (Institute for the Study of Labor (IZA), 2013)
Economics has been shown to be a relatively high earning college major, but geographic differences in earnings have been largely overlooked. This paper uses the American Community Survey to examine geographic differences in both absolute earnings and relative earnings for economic majors. We find that there are substantial geographic differences in both the absolute and relative earnings of economics majors even controlling for individual characteristics such as age and advanced degrees. We argue that mean earnings in specific labor markets are a better measure of the benefits of majoring in economics than simply looking at national averages.
Keywords: I23; J24; J31; R23; 330; economics major; earnings differentials; college education; local labor markets